Benin : Poverty Reduction Strategy Paper; Growth Strategy for Poverty Reduction. (IMF Staff Country Reports; Country Report, 2008)
Benin has been implementing a national poverty reduction strategy for sustainable human development. The government of Benin judiciously stressed the development of the social sector and improved governance to develop human resources and enhance the effectiveness of its actions so as to lay the foundations for sustainable human development. The sectoral strategies and policies growing out of the poverty reduction and growth strategy (SCRP) will be refined and/or readjusted to more clearly delineate the actions planned and thereby facilitate their implementation.